Influence of Dark Matter Subhalos on the Formation of the Galaxy Spiral Arms (2025)
The dynamical stability of disk galaxies in a ΛCDM cosmology is a fundamental topic in galactic evolution, particularly in the presence of perturbers. In this study, we analyze the structural and kinematic properties of a simulated galactic disk, focusing on the effects of satellite interactions on key dynamical quantities and their influence on the formation of spiral structures. Using high-resolution numerical simulations with the GIZMO multiphysics code, we evaluate the evolution of circular velocity, epicyclic frequency, shear rate, velocity dispersions, and the Toomre stability parameter. Our simulations incorporate the self-gravity of the stellar disk and gas, along with the full physics of star formation, feedback, and metal cooling in the ISM. Dark matter subhalos interactions are modeled using a population that follows the distribution of mass and orbital parameters observed in cosmological simulations of galaxy formation. The experimental setup includes 30 simulations, ranging from isolated (control) cases to full mergers where the disk interacts with subhalos. To distinguish numerical effects from true dynamical impact, each bombarded simulation is compared to its corresponding isolated counterpart. Key dynamical tracers show stable behavior, and the overall impact of subhalos on the disk’s structure appears minimal. No strong evidence is found that subhalos induce the formation of long-lived spiral arms, especially in simulations that include full baryonic physics. Several factors may contribute to this result. The population of subhalos has relatively low masses and large pericenter distances, limiting their gravitational influence. The string supernova feedback model depletes the gas disk early, preventing sustained spiral structure formation. Additionally, assuming a rigid halo prevets dynamical friction from altering satellite orbits, biasing interactions toward weaker perturbations. Our findings highlight key aspects of galactic evolution. Feedback modeling plays a crucial role in the longevity of spiral structures, while the mass and orbital properties of subhalos significantly influence their perturbative effects. The assumption of a rigid halo mat underestimates the impact of minor mergers by preventing subhalos from sinking toward the disk center. Despite these considerations, our results suggest that the bombardment of subhalos could still provide a natural mechanism for generating transient, fragmented spiral structures in galactic disks.